SISTEM MONITORING KEHADIRAN DOSEN DALAM PROSES BELAJAR MENGAJAR DI STMIK NEUMANN MEDAN B ERBASIS ANDROID - Krismonika Br Sitepu; Mahdianta Pandia (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2019)
Monitoring is the activity of assessing work patterns carried out by studying and observing anactivity carried out in accordance with the plan.The monitoring system is very important in allagencies, the monitoring system can help the parties involved in information retrieval or decisionmaking. Attendance is one of the most important things in an agency, therefore in an agency amonitoring system for attendance is very important to be implemented so that every employee whoworks in a particular institution will discipline time. Seeing the development of technology today,all humans want to do everything quickly, one that can be created to monitor attendance is to usean android application.Monitoring is the activity of assessing work patterns carried out by studyingand observing an activity carried out in accordance with the plan.